Response Surface Methodology (RSM) for Optimization Carbonization Parameters of Exhausted Coffee Husk for Iron Removal from Aqueous Solution - Puari, Aninda T.; Yanti, Nika R.; Sari, Nurmala; Rusnam, Rusnam (The University of Lampung, 2024)
In this study, biochar derived from exhausted coffee husk (ECH) was used as biosorbent for removing Iron (II) from aqueous solution. The aim of this study was to improve the biosorption capacity of the biosorbent from agricultural solid waste and its usability for Fe²⁺ removal. The biosorption performance of ECH biochar was optimized through carbonization parameters: temperature, time, and temperature gradient. Response Surface Methodology (RSM) based on multivariate analysis was employed to evaluate the biosorption performance of ECH biochar for Fe²⁺ biosorption. The optimum performance predicted through Box-Behnken design experiment. The optimal combination of the three parameters was 549.37°C, 1.98 h and 21.98°C/min. At the optimal condition the removal efficiency (RE) was predicted to be 107.01% and biosorption capacity (qt) was 5.11 mg/g. SEM-EDX, FT-IR and XRD analysis were conducted in this study to evaluate the biosorption mechanism of ECH biochar on the iron ion. The results showed that ion exchange existed on the surface of the ECH biochar during the biosorption. Additionally, the presence of functional groups on the ECH biochar surface responsible for Fe(II) binding. Overall, the findings of this study suggested an eco-friendly strategy for optimizing the removal of Iron (II) from polluted water by the biosorption onto ECH biochar. Keywords: Biochar, Biosorption capacity, Box-Behnken design, Temperature, Time